Stock market consequences of the suspension of the Central Bank of Nigeria's Governor - Mohammed, Ibrahim (Managing global transitions, 2014)
The sudden announcement of the suspension of the Governor of the Central Bank of Nigeria (CBN) on the 20th February 2014 created mixed reactions among analysts and market participants in Nigeria and beyond. The objective of this study is to empirically establish the reaction of listed firms' stock prices to the announcement of the suspension of the Governor of the CBN. Using the standard event study methodology on a sample of 104 out of the 122 listed firms that traded on the floor of the nse on the fateful day, the study sought to establish the significance of abnormal return and cumulative abnormal return on the announcement day, and fifteen trading days after the announcement became public. The study found the presence of statistically significant abnormal return and cumulative abnormal return of -0.06 percent and -5.95 percent on the announcement day. It also established the presence of statistically significant cumulative abnormal return of approximately -6.91 percent fifteen trading days after the announcement. The study concluded that the sudden announcement of the suspension of the Governor of the CBN gave rise to a negative market reaction by listed firms in Nigeria, and the negative trend persisted for the fifteen trading days after the announcement. It was recommended that subsequently, policy makers should as much as possible avoid sudden announcements of the suspension or removal of the Chief Executive Officers (CEOs) of public institutions that have close links with the stock market. Where the need for such action becomes inevitable, the announcement should be preceded by the release of information that will minimize asymmetry between policy makers and the stock market.
Keywords: borze; delnice; cene delnic; banke; Centralna banka Nigerije; guverner CBN; študije dogodkov; stock prices; Governor of the CBN; event studies